2018
DOI: 10.3892/ol.2018.7937
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑21‑5p induces the metastatic phenotype of human cervical carcinoma cells in vitro by targeting the von Hippel‑Lindau tumor suppressor

Abstract: Abstract. Numerous studies have indicated that microRNAs (miRs), a group of small non-coding RNAs, are determining regulatory elements involved in the pathogenesis of various types of cancer, including cervical cancer (CC). Although miR-21-5p upregulation has been demonstrated to associate with tumorigenesis by controlling the expression of oncogenic and tumor suppressor genes, only a small number of studies have investigated the expression of miR-21-5p and its functional role in CC. The objective of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…MiR-21-5p was confirmed to be highly expressed and plays its oncogene roles in a variety of tumors, including BC 16 18 . For example, miR-21-5p advanced migration and invasion of cervical carcinoma cells through targeting von Hippel-Lindau tumor suppressor (VHL) gene 19 . But the effects of miR-21-5p on malignant cellular phenotypes of BC are not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-21-5p was confirmed to be highly expressed and plays its oncogene roles in a variety of tumors, including BC 16 18 . For example, miR-21-5p advanced migration and invasion of cervical carcinoma cells through targeting von Hippel-Lindau tumor suppressor (VHL) gene 19 . But the effects of miR-21-5p on malignant cellular phenotypes of BC are not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…In the UM samples, 423 mature miRNAs were shown to be present, of which 13 miRNAs were differentially expressed between low-, intermediate- or, high-risk UM. MiRNAs that are highly expressed in high-risk UM include several known oncomirs such as miRNA-17-5p [25,26,27], miRNA-151a-3p [28], and miRNA-21-5p [29,30,31,32]. MiRNA-17-5p has been described to promote cell proliferation, invasion, and metastasis through several mechanisms, such as PTEN repression, downregulation of EGFR2, and TGFBR2 targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-21 may act as an oncogene that is overexpressed and hyperactivated in a variety of cancer types, and that its upregulation promotes the proliferation, apoptosis, invasion and chemoresistance by targeting numerous tumor suppressor genes, including phosphatase and tensin homologue, programmed cell death 4, tissue inhibitor of metalloproteinases 3, tropomyosin 1, ras homolog gene family member B and maspin ( 24 28 ). It appears that the majority of studies has considered miR-21-5p a cancer-promoting ‘oncomiRs’ that drives tumor progression and development ( 29 , 30 ). The present study, however, indicated that downregulated miR-21-5p expression may be associated with the peritoneal metastatic potential of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%